Hubungan Antara Tingkat Pendidikan dan Lama Berjualan dengan Pengetahuan Pedagang Bakso tentang Bahan Tambahan Pangan - Amirah Maulida Rohmah; Trias Mahmudiono (Media Gizi Kesmas, 2023)
Background: Meatballs are one of the most popular foods in Indonesia. There are many consumers so meatballs seller can be found in every area. The advanced technology has led to the expansion of meatball marketing through online delivery platforms such as Grabfood and Gofood. However, there are many sellers still using prohibited food additives in their products. Objectives: This study aimed to analyze the association between level of education and selling experience with knowledge about food additive in meatballs (Bakso) seller who using the online food delivery platform such as Grabfood and Gofood in East Surabaya. Methods: This study used cross-sectional design. The sample sizes were 46 meatball sellers recruited through simple random sampling. The data collected including characteristics of respondents (age, gender, platform online and income), level of education, selling experience and level of knowledge about food additive. The result was analyzed using Rank Spearman Test and Pearson test. Results: Most of the respondents had good formal education and low knowledge. The result of statistical calculation using Spearman test showed that there was no significant correlation (p=0.187) between level of education with seller's knowledge. In addition, Pearson test showed that there was no significant correlation (p=0.188) between selling experience with seller's knowledge. Conclusions: There was no significant correlation between level of education and selling experience with the knowledge about food additive of meatball sellers who using online food delivery platforms. Therefore, increasing the knowledge of meatball sellers about food additives through various media such as television, magazines, billboards and other sources of information is needed.